Nonlinear microwave circuit design - Giannini, Franco, 1944- (J. Wiley & Sons, 2004)
"Nonlinear microwave circuits form the building blocks of key components in wireless communications devices. This book presents the theory and practical design methodology for some of the most common nonlinear microwave circuits including power amplifiers, oscillators, mixers, frequency multipliers and dividers." "Nonlinear Microwave Circuit Design will appeal to practising microwave engineers and circuit designers, senior undergraduates, graduate students and researchers in microwave and communications engineering."--Jacket